2021
DOI: 10.4103/jehp.jehp_467_20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of flipped classroom model in teaching histology for first-year MBBS students based on competency-based blended learning

Abstract: BACKGROUND: With recent changes in the curriculum of bachelor of medicine and bachelor of surgery (MBBS) course to meet the global trends and to fulfill the standards expected from an Indian medical graduate, introduction of newer teaching methodologies becomes mandatory. The usage of flipped classroom (FCR) in medical education has always been rewarding. This study was to evaluate the effectiveness of FCR as a teaching method in comparison with traditional lectures in histology sessions in Sri Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Perceived strengths and benefits of blended learning in Anatomy education can be grouped into three common themes; namely, the strengths/benefits related to the acquisition and development of learning competencies, related to the learning process, and the instructional material. The most commonly reported benefits of blended learning were the improvement of anatomy knowledge and knowledge consolidation (16,17,19,(25)(26)(27)(28), promotion of self-directed learning (16,20,22,25,27), flexibility in time, place and pace of learning (16,18,20,22,24,25,27),…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived strengths and benefits of blended learning in Anatomy education can be grouped into three common themes; namely, the strengths/benefits related to the acquisition and development of learning competencies, related to the learning process, and the instructional material. The most commonly reported benefits of blended learning were the improvement of anatomy knowledge and knowledge consolidation (16,17,19,(25)(26)(27)(28), promotion of self-directed learning (16,20,22,25,27), flexibility in time, place and pace of learning (16,18,20,22,24,25,27),…”
Section: Resultsmentioning
confidence: 99%
“…This highlights the need for careful selection, planning and delivery of online teaching-learning activities and online learning material in a way that promotes communication and interaction among students and with the teachers. Most of the studies reported the continuation of the traditional practice of gross anatomy, histology, radiological anatomy and living anatomy laboratory sessions with instructorled discussions, small group discussions and small group laboratory activities that provided opportunities for collaboration and communication, and these were well-received by the students in the blended learning courses (15)(16)(17)(18)(19)(21)(22)(23)(24)26,28,29). Several studies reported the use of online discussions forums to compensate for reduced time allocation for in-class interactions (18,22,24,31), and possibility of using social networking and messaging applications to improve communication and interaction in the blended learning approach was also shown (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is the first to describe the enhancement of learning from a flipped classroom approach in Project ECHO. Previous studies of UG medical students in India have described the positive benefits of a flipped classroom on learning, showing improvements in learners' knowledge, as well their enthusiasm for the design (Aristotle et al 2021;Sreegiri et al 2018). In this study, PG learners enthusiastically embraced the flipped classroom, suggesting that a flipped classroom is a highly valued learning format for PG learners in this setting.…”
Section: Flipped Classroommentioning
confidence: 99%